A study of newborn on prelacteal feeds - Hirekerur, Vikram L.; Kulkarni, Atul A.; Hirekerur, Tanvi V. (International Journal of Contemporary Pediatrics, 2017)
Background: Infants are often prescribed prelacteal feeds after birth. We studied 50 such cases. Most prescriptions were written on day one. Maternal problems were the commonest reasons cited. However maternal and neonatal diseases severe enough to affect lactation are rarely encountered. On counselling breastfeeding was initiated. The seeds of lactation failure are sown on day one of life. The best chance of preventing it is on day one. Methods: 50 newborn babies born between August 2015 and July 2016 in Ashwini Rural Medical College and Hospital, Kumbhari, Solapur, Maharashtra, India and who were prescribed prelacteal feeds were included in the study. Approval from ethical committee was taken. Results: Most mothers did not have any medical or pregnancy related diseases. Antenatal counselling was not done in 18 (36 %) mothers. In 48 (96%) cases prelacteal feeds were initiated on day one. Maternal problems 19 (38%) were the commonest reasons cited for prelacteal feeds. In majority of cases 45 (90 %) there was no neonatal reason for prelacteal feeds. 22 (44 %) mothers initiated breastfeeding on recovery from their medical problems. In 17 (34%) cases, counselling was done and was effective. Conclusions: Prelacteal feeds are commonly prescribed in postnatal wards. Maternal problems were the commonest reasons cited though most of the mothers did not have medical or pregnancy related disease. Proper counselling was effective in convincing mothers. Maternal and neonatal diseases severe enough to affect lactation are rarely encountered. Antenatal counselling is an effective way to initiate breastfeeding on day one.